Value based pricing on customer value - Wilkinson, Mike (Henry Stewart Talks, 2010)
Value measures, Customer value map, Value line, Customer value, Value perception, Cost reduction, Revenue gain, Increasing revenue, Building profitability, Growing profitability, Profit building, Revenue growth, Profit growth, Differentiation, Price building, Competitive pricing, Reference pricing, Emotional contribution, Emotions, Value in use, How to price effectively, Pricing methods, Pricing approaches